The role of computed tomography in the classification and management of pelvic fractures - Draffan, D.; Clements, D.; Farrell, M.; Heller, J.; Bennett, D.; Carmichael, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
Computed tomography (CT) imaging is an important component in the pre-operative assessment of pelvic fractures in humans. The value of CT images in the management of small animal pelvic fractures is presently undetermined. The objective of this study was to investigate the benefits of CT images on the management of pelvic fractures. A prospective study of 25 traumatised cases of canine and feline pelvic fractures were evaluated, where CT images and conventional orthogonal radiographic assessments were performed on each case. Three diplomat orthopaedic surgeons independently reviewed the radio-graphs and CT images on separate occasions and determined fracture classification, management plan, estimated recovery time and prognosis. A consensus review of the imaging modalities and surgical reports was used as the definitive fracture description. For all observers, management was not found to differ significantly between radiographic and CT analysis (P< 0.05). There was moderate agreement between observers and between imaging modalities for fracture description. Greatest discrepancy was found as the fracture complexity increased, such as with acetabula and sacral fractures, whereby CT was the most sensitive. Clinically high quality radiography would be recommended for all pelvic fracture cases; CT may be beneficial where there is uncertainty, particularly with acetabula fractures or sacral fractures causing neurological deficits. Experienced orthopaedic surgeons often disagreed on the diagnosis, treatment and prognosis of pelvic trauma.
Keywords: CT; pelvic fractures; canine; feline; fracture classification